Self-esteem and Self-concept as Predictors of Social Anxiety in University Students - Hume Figueroa , Miriam Ruth (2025)
Social anxiety is currently recognized as having an inverse relationship with self-esteem in university students. However, the effect of self-concept on this relationship has been little studied. This study explores the influence of self-esteem and self-concept (academic, social, emotional, family, and physical) on social anxiety, as self-reported by university students. It distinguishes between dimensions such as fear of public speaking/interacting with authority figures, interacting with strangers, interacting with the opposite sex, assertive expression of annoyance, disgust or displeasure, and sensitivity to criticism and embarrassment. The study employed a non-experimental, cross-sectional, and correlational design. Participants included  282 students from the faculty of education (58 men and 224 women), aged between 18 and 40 years. They completed the Social Anxiety Questionnaire for Adults, the Self-Esteem Scale, and the AF-5 Self-Concept Inventory. Multiple regression revealed that emotional and social self-concept predict most dimensions of social anxiety, often with a greater effect than self-esteem. The results suggest that students' perceptions of themselves have a more substantial impact on social anxiety than their self-assessed sense of worth. Intervention programs focusing on emotional and social self-concept, while accounting for individual, cultural, and gender differences, may effectively reduce social anxiety in this demographic.